2010
DOI: 10.1037/a0021556
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of forebrain neuronal glycine transporter 1 disruption in the senescent brain: Evidence for age-dependent phenotypes in Pavlovian learning.

Abstract: Genetic deletion of glycine transporter 1 (GlyT1) in forebrain neurons gives rise to multiple procognitive phenotypes, presumably due to enhanced N-methyl-D-aspartate receptor (NMDAR) functions. However, concerns over possible harmful excitotoxic effects under life-long elevation of synaptic glycine have been raised. Such effects might accelerate the aging process, weakening or even reversing the pro-cognitive phenotypes identified in adulthood. Here, we examined if one of the most robust phenotypes in the mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…Yet, there was no evidence that the extinction of CS-freezing was more rapid in the mutants (Figure 3A). This is consistent with our impression obtained in our previous studies on conditioned freezing with this mutant mouse line [24]. …”
Section: Discussionsupporting
confidence: 94%
“…Yet, there was no evidence that the extinction of CS-freezing was more rapid in the mutants (Figure 3A). This is consistent with our impression obtained in our previous studies on conditioned freezing with this mutant mouse line [24]. …”
Section: Discussionsupporting
confidence: 94%
“…This finding agrees with the anxiolytic profile of the GlyT1 inhibitor SSR504734 which was obtained in male animals tested during the light phase (Depoortère et al, 2005). At the same time, the lack of such anxiety effects in the dark phase agrees with previous reports based solely on results obtained in this phase (Yee et al, 2006), and therefore anxiety did not confound the previously established phenotypes (Dubroqua et al, 2010; Singer et al, 2007, 2009; Yee et al, 2006). This new finding in the elevated plus maze may be interpreted as a state-dependent genotypic effect, revealed here by the explicit comparison between mice kept in opposite light-dark cycles but tested at the same time under identical test conditions.…”
Section: Discussionsupporting
confidence: 91%
“…However, although the initial report of an enhanced Pavlovian conditioning phenotype in GlyT1 ΔFBNeuron mice has been demonstrated across three conditioning paradigms, the paradigms were all aversive in nature and the reported data were exclusively derived from female subjects maintained in a reversed light-dark cycle to allow testing in the dark phase (Yee et al, 2006). Although there is evidence that this phenotype is present in both sexes and persisted into old age (Dubroqua et al, 2010), some data suggested that the phenotype might be somewhat weaker statistically in the male sex (Philipp Singer, personal communication).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological and genetic manipulation of the glycine transporter-1 (GlyT-1) can alter extracellular glycine concentrations and subsequently influence NMDA receptor activity (Chen et al, 2003;Kinney et al, 2003;Dubroqua et al, 2010). It has been proposed that compounds that elevate extracellular glycine via inhibition of GlyT-1 activity can ameliorate cognitive deficits (Liem-Moolenaar et al, 2010;Wallace et al, 2011;Nikiforuk et al, 2011;Singer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%